2014
DOI: 10.1200/jco.2013.49.9020
|View full text |Cite
|
Sign up to set email alerts
|

Deep Molecular Response Is Reached by the Majority of Patients Treated With Imatinib, Predicts Survival, and Is Achieved More Quickly by Optimized High-Dose Imatinib: Results From the Randomized CML-Study IV

Abstract: MR(4.5) is a new molecular predictor of long-term outcome, is reached by a majority of patients treated with imatinib, and is achieved more quickly with optimized high-dose imatinib, which may provide an improved therapeutic basis for treatment discontinuation in CML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
254
2
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(271 citation statements)
references
References 35 publications
(33 reference statements)
13
254
2
2
Order By: Relevance
“…Imatinib is recognized as one of the best and safest first line treatments for chronic phase CML [5][6][7] and is associated with a normal or near-normal life expectancy among treated patients [8,9], even at diagnosis [10]. Imatinib induces complete cytogenetic response (CCyR) in up to 86% of CML patients, while major molecular responses (MMR) develop in 33-90% of the patients according to treatment duration [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Imatinib is recognized as one of the best and safest first line treatments for chronic phase CML [5][6][7] and is associated with a normal or near-normal life expectancy among treated patients [8,9], even at diagnosis [10]. Imatinib induces complete cytogenetic response (CCyR) in up to 86% of CML patients, while major molecular responses (MMR) develop in 33-90% of the patients according to treatment duration [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…With 5 years of follow-up in ENESTnd, 54% of patients in the nilotinib 300-mg twice-daily arm achieved MR 4.5 and 96% of patients had freedom from progression to AP/BC (vs. the imatinib arm: 31% [P < 0.0001] and 92% [P 5 0.0403], respectively) [16]. Retrospective landmark analyses of other independent clinical trials have demonstrated similar associations between deeper molecular responses and improved OS, event-free survival, and failure-free survival [20,29,35]. For example, patients who achieved a confirmed MR 4.5 at 4 years on frontline imatinib in the German CML IV trial had significantly higher OS at 8 years than patients who did not achieve this level of stable molecular response [20].…”
Section: Importance Of Achieving Deep Molecular Responses To Tki Therapymentioning
confidence: 97%
“…The latest NCCN guidelines recommend additional monitoring to detect any disease progression and the consideration of a change in the treatment regimen when BCR-ABL1 IS is > 10% at the 3-month time point [7]. This recommendation is based on several retrospective landmark analyses that show the prognostic significance of early molecular response with TKIs [9,[20][21][22][23]. As a result of these changes in response criteria, recommendations for monitoring responses, including molecular responses, are also evolving.…”
mentioning
confidence: 99%
“…Similarly, molecular response is assessed at 3,6,12 and 18 months and thereafter periodically for follow-up. It is evident from the literature that the patients who have suboptimal cytogenetic or molecular response at a given point of time fare poorly in the long run [32][33][34]. Interpretation of these tests and alteration in treatment for management of suboptimal response is out of purview of this article.…”
Section: Chronic Myelogenous Leukemia (Cml)mentioning
confidence: 99%